2012
DOI: 10.1002/sd.463
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable development as a community of practice: insights from rural water projects in Egypt

Abstract: A community-of-practice (CoP) approach is used to analyze rural water sustainability. In combining CoP with the capability approach (CA), a dichotomy is generated between project goals and project practices and whether they are locally or externally driven. Four possible project scenarios are developed from this framework: empowerment (local goals and practices), apprenticeship (local practices and external goals), assistencialism (external practices and local goals) and determinism (external goals and practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…In this paper, metasynthesis was used to determine the SSCM performance indicators (Sandelowski & Barroso, ). Metasynthesis is a qualitative method that, through a systematic approach, combines selected studies to discover new subjects and enhance knowledge (Armanios, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, metasynthesis was used to determine the SSCM performance indicators (Sandelowski & Barroso, ). Metasynthesis is a qualitative method that, through a systematic approach, combines selected studies to discover new subjects and enhance knowledge (Armanios, ).…”
Section: Methodsmentioning
confidence: 99%
“…Metasynthesis is a qualitative method that, through a systematic approach, combines selected studies to discover new subjects and enhance knowledge (Armanios, 2012). The reason for choosing metasynthesis approach is that it can help discover the new and fundamental themes and metaphors by providing the researchers with a systematic frame and by combining different researches and consequently making it possible to have a comprehensive perspective toward issues (Serdarasan, 2013).…”
Section: Metasynthesis Approachmentioning
confidence: 99%
“…Previous studies focused on the environmental aspects of sustainability in project deliverables while giving less attention to sustainable project management during project delivery [13]. Armanios [14] believed that if we are to possess a more complete and holistic view of sustainability, engineering sustainability needs to be considered and discussed more. At present, few investigations are available on the sustainability of PPP infrastructure projects.…”
Section: Introductionmentioning
confidence: 99%
“…In another study from Indonesia the authors concluded that micro hydro projects perform well in most sustainability indicators except economic, as they do not have an economic scheme in place (Purwanto & Afifah, 2016). Armanios (2012) proposed three sets of indicators economic, engineering, and environmental to assess three village water projects in Egypt. The innovation of his approach is the use of a framework that includes the community‐of‐practice (CoP) approach and the capability approach (CA), while he distinguishes between project goals and practices.…”
Section: Literature Reviewmentioning
confidence: 99%